2022
DOI: 10.3389/fnbeh.2022.828566
|View full text |Cite
|
Sign up to set email alerts
|

Signal Detection Theory as a Novel Tool to Understand Cognitive Fatigue in Individuals With Multiple Sclerosis

Abstract: Multiple Sclerosis (MS) affects 2.8 million persons worldwide. One of the most persistent, pervasive, and debilitating symptoms of MS is cognitive fatigue. While this has been known for over a century, cognitive fatigue has been difficult to study because patients’ subjective (self-reported) cognitive fatigue has consistently failed to correlate with more objective measures, such as reaction time (RT) and accuracy. Here, we investigated whether more nuanced metrics of performance, specifically the metrics of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
(86 reference statements)
1
4
0
Order By: Relevance
“…Lastly, cognitive fatigue rate was found to be associated with trait cognitive fatigue, but not depression, anxiety, whole brain lesion volume, SDMT performance, or performance during a fatigue inducing task (i.e., RT, accuracy). The latter is consistent with previous examinations showing that performance measures, such as reaction time and accuracy, are weakly correlated with fatigue ratings ( 66 – 68 ).…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, cognitive fatigue rate was found to be associated with trait cognitive fatigue, but not depression, anxiety, whole brain lesion volume, SDMT performance, or performance during a fatigue inducing task (i.e., RT, accuracy). The latter is consistent with previous examinations showing that performance measures, such as reaction time and accuracy, are weakly correlated with fatigue ratings ( 66 – 68 ).…”
Section: Discussionsupporting
confidence: 92%
“…Within-subject 2 × 3 repeated-measures ANOVAs were conducted for the dependent variables: reaction times, accuracy and indexes established by signal detection theory (sensitivity and response bias) . Signal detection analysis was conducted to separate sensitivity from response bias, which could independently affect the accuracy [ 40 ]. This analysis was necessary when exploring which process was influenced by the effective states.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, apart from overall accuracy, signal detection metrics were reported: sensitivity and response bias, which could independently influence accuracy [ 40 ]. It is interesting to note in both tasks, the impairment effects of high avoidance-motivational intensity on accuracy, sensitivity and response bias were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we have argued that CF is related to a change in the balance between effort and reward 54,57,58 . That is, CF is related to maintaining an aspect of homeostasis whereby the effort expended merits the reward received.…”
Section: Discussionmentioning
confidence: 95%
“…An LME was used (3dLMEr from the AFNI suite of processing tools) with Task (2-back vs. mSDMT), Sex (men vs. women) and Run (runs 1-4) as factors; the VAS-F scores, and age were included as quantitative variables; participant was included as a random factor. As in previous work 15,21,54,55 only runs resulting in CF were included in the analysis (i.e., runs in which the VAS-F score was greater than zero). This resulted in the exclusion of ~ 20% of runs (see supplemental data section details).…”
Section: The Relationship Between Cf and Brain Atrophymentioning
confidence: 99%